Hohle Fels – A UNESCO Global Geopark Geosite within a UNESCO World Heritage Site: Protection and Cooperation - Conny Meister; Iris Bohnacker; Guido Bataille (Geoconservation Research)
The Hohle Fels Cave in the Swabian Jura is a key site of the Central European late Middle and early Upper Paleolithic. The Aurignacian deposits with more than 90,000 lithic artifacts, numerous faunal remains as well as the presence of flutes, beads and mobile art objects, give an exceptional insight into the material culture between 42,000 and 35,000 years B.P. Since 2017, the site has been part of the UNESCO World Heritage “Caves and Ice Age Art in the Swabian Jura”. Situated within the central Swabian Jura, the cave is also an integrative part of the Swabian Alb UNESCO Global Geopark. Based on cultural phenomena and geological peculiarities, the management teams of the World Heritage and the Geopark work together on the establishment of a management plan and the implementation of protective and monitoring measures. Future cooperation projects between the Geopark and World Heritage site in terms of management and development of a shared protection program are the logical consequence of the dual cave protection.